An American pickle [videorecording (DVD)] - Rich, Simon; Rogen, Seth, 1982-; Snook, Sarah, 1987-; Rich, Simon (Warner Bros. Entertainment Inc., 2022)
An American Pickle stars Seth Rogen as Herschel Greenbaum, a struggling labourer who immigrates to America in 1919 with dreams of building a better life for his beloved family. One day, while working at his factory job, he falls into a vat of pickles and is brined for 100 years. The brine preserves him perfectly and when he emerges in present day Brooklyn, he finds that he hasn't aged a day. But when he seeks out his family, he learns that his only surviving relative is his great-grandson Ben Greenbaum (also played by Rogen), a mild-mannered computer coder whom Herschel can't even begin to understand.